COMPARATIVE ANALYSIS OF SPUN PILE CARRYING CAPACITY IN KAMAL-TELUK NAGA-RAJEG (KATARAJA) TANGERANG TOLL ROAD CONSTRUCTION PROJECT - Aep Catur Wahyudi; Gotot Slamet Mulyono (Jurnal Ekonomi, 2023)
The foundation is the bottom structure in a building, therefore the foundation is a very important part of the structure in building construction. Foundation construction needs to be carried out bearing capacity analysis to avoid structural failure/damage. The Kamal-Teluk Naga-Rajeg Toll Road (KATARAJA) construction project uses a spun pile type foundation. Analysis of pile bearing capacity can be carried out by using static testing, dynamic testing, and empirical testing. In this study to calculate the analysis of the bearing capacity of the piles used dynamic tests, namely the Standard Penetration Test (SPT), Pile Driving Analysis (PDA) and Calendering. Spun pile bearing capacity from SPT data was calculated using the Luciano Decourt and Tomlinson methods. In the PDA test, an analysis of the interpretation of the PDA results is carried out. The carrying capacity of the spun pile from the Calendering data was calculated using the Hiley method, and the Engineering News Record (ENR). In testing the SPT test was carried out at 2 points, namely the PB-48 point and the PB-49 point. The PDA test was carried out on PSL 8-38 piles and PSL points 8-39. Calendaring calculations in this study were carried out at PSL 8-38 piles and PSL points 8-39. The results of the comparison between the carrying capacity of the spun pile using SPT data using the Luciano Decourt method and PDA Interpretation obtained the closest results, namely PB-48 pile of 61%, the Tomlinson method, namely PB-49 pile of 62%. The comparison between the carrying capacity of the spun pile using Calendering data and the closest PDA interpretation is the Hiley method for PSL8-39 piles of 31%, the ENR method, namely PSL 8-38 piles of 36%. The results of the comparison between the carrying capacity of the spun pile using the average SPT data and Calendering data obtained the closest result, namely using the Hiley method on pile PB-48 of 42%, and the ENR method on pile PB-48 of 48%.